2019
DOI: 10.3389/fnsys.2019.00048
|View full text |Cite
|
Sign up to set email alerts
|

Neural Representation of Overlapping Path Segments and Reward Acquisitions in the Monkey Hippocampus

Abstract: Disambiguation of overlapping events is thought to be the hallmark of episodic memory. Recent rodent studies have reported that when navigating overlapping path segments in the different routes place cell activity in the same overlapping path segments were remapped according to different goal locations in different routes. However, it is unknown how hippocampal neurons disambiguate reward delivery in overlapping path segments in different routes. In the present study, we recorded monkey hippocampal neurons dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…While parietal neurons seem to code a reaching space centered on the head [ 52 , 56 , 57 ], and hippocampal cells code a navigation space based on distal cues and reward locations [ 73 , 74 , 75 ], the SII appears to situate the whole body in the surrounding environment [ 60 ]. As the SII codes not only the separate body parts as a source of somatosensation but also a combination of those body parts into an indivisible concept of an individually and socially aware self-body, both mirror recognition and self/non-self differentiation could be explained along the observed sensory responses.…”
Section: Discussionmentioning
confidence: 99%
“…While parietal neurons seem to code a reaching space centered on the head [ 52 , 56 , 57 ], and hippocampal cells code a navigation space based on distal cues and reward locations [ 73 , 74 , 75 ], the SII appears to situate the whole body in the surrounding environment [ 60 ]. As the SII codes not only the separate body parts as a source of somatosensation but also a combination of those body parts into an indivisible concept of an individually and socially aware self-body, both mirror recognition and self/non-self differentiation could be explained along the observed sensory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Although we focus here on spatial trajectories, splitting has also been observed on non-spatial tasks such as those presenting overlapping sequences of discrete odor cues (Ginther et al, 2011;Shahbaba et al, 2022) indicating that the phenomenon is quite general 2 . Similarly, although typical splitter studies use tetrode recordings in rats, trajectory splitting has also been found using calcium imaging in mice (Kinsky et al, 2020;Levy et al, 2021; see also Nieh et al, 2021;Keinath et al, 2020;Sun et al, 2020), using recordings in macaques (Bretas et al, 2019;Gulli et al, 2020) and with intracranial recordings (Ekstrom et al, 2003) and fMRI in humans (Brown et al, 2016(Brown et al, , 2010; see also : Hsieh et al, 2014).…”
Section: Splitting At the Single Cell And Ensemble Levelmentioning
confidence: 99%
“…The animal sat in a monkey chair with a stereotaxic frame during the recording session. The monkey's head was then painlessly fixed with the stereotaxic frame by fixing a U-shaped frame that was previously implanted into the animal's skull [30] [33] . During neuronal recording, the left eye positions of the animal were tracked by an eye-tracking system using a CCD camera with a 150 Hz time resolution [34] .…”
Section: Monkey Virtual Spatial Navigation Paradigmmentioning
confidence: 99%
“…In the FP-VN task, a 3D open space (diameter, 180 m), which was constructed using 3D software (EON Studio ver. 2.5.2, EON Reality, USA), was used [31] [33] ( Fig. 1B ).…”
Section: Monkey Virtual Spatial Navigation Paradigmmentioning
confidence: 99%
See 1 more Smart Citation